Nonstandard Echocardiographic Examination - Nanda, Navin C; Sungur, Aylin; Bhagatwala, Kunal; Karia, Nidhi M; Öz, Tuðba Kemaloðlu (Cardiovascular Journal, 2014)
In addition to standard echocardiographic planes, there are many so-called nonstandard echocardiographic examination windows and planes that have been found useful in clinical practice. Standard planes have also been utilized with or without modification to find structures not routinely detected during echocardiographic examination. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18347 Cardiovasc. j. 2014; 6(2): 92-102